The DmsABC S-oxide reductase is an essential component of a novel, hypochlorite-inducible system of extracellular stress defense in Haemophilus influenzae - Nasreen, Marufa; Ellis, Daniel; Hosmer, Jennifer; Essilfie, Ama-Tawiah; Fantino, Emmanuelle; Sly, Peter; McEwan, Alastair G.; Kappler, Ulrike (Frontiers in Microbiology, 2024)
Defences against oxidative damage to cell components are essential for survival of bacterial pathogens during infection, and here we have uncovered that the DmsABC S-/N-oxide reductase is essential for virulence and in-host survival of the human-adapted pathogen, Haemophilus influenzae. In several different infection models, H. influenzae DdmsA strains showed reduced immunogenicity as well as lower levels of survival in contact with host cells.Expression of DmsABC was induced in the presence of hypochlorite and paraquat, closely linking this enzyme to defence against host-produced antimicrobials. In addition to methionine sulfoxide, DmsABC converted nicotinamide-and pyrimidine-N-oxide, precursors of NAD and pyrimidine for which H. influenzae is an auxotroph, at physiologically relevant concentrations, suggesting that these compounds could be natural substrates for DmsABC.Our data show that DmsABC forms part of a novel, periplasmic system for defence against host-induced S-and N-oxide stress that also comprises the functionally related MtsZ Soxide reductase and the MsrAB peptide methionine sulfoxide reductase. All three enzymes are induced following exposure of the bacteria to hypochlorite. MsrAB is required for physical resistance to HOCl and protein repair. In contrast, DmsABC was required for intracellular colonization of host cells and, together with MtsZ, contributed to resistance to N-Chlorotaurine. Our work expands and redefines the physiological role of DmsABC and highlights the importance of different types of S-oxide reductases for bacterial virulence.